2007
DOI: 10.7205/milmed.172.12.1250
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Risk Assessment and Preventive Recommendations: A New Approach for the Canadian Military

Abstract: Western militaries deploying to international locations are often confronted with the threat of malaria. For the Canadian military, the consequent response has been prescriptive-any risk of malaria warrants use of personal protective measures and chemoprophylaxis. In reality, however, malaria risk is highly variable and a one-size-fits-all strategy to mitigation may not be appropriate. In line with this, the Canadian military has revised its approach to malaria risk assessment and preventive response. More eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…About this matter, a predictive modeling suggested that the risk of malaria among Canadian forces in Afghanistan was similar or even lower than the expected incidence of SAEs for some chemoprophylactic regimens, particularly mefloquine; hence the discontinuation. 34 Another important issue is the use of primaquine terminal prophylaxis. This procedure seems to be prescribed only within several coalition contingents.…”
Section: Chemoprophylaxis Compliance and Tolerabilitymentioning
confidence: 99%
“…About this matter, a predictive modeling suggested that the risk of malaria among Canadian forces in Afghanistan was similar or even lower than the expected incidence of SAEs for some chemoprophylactic regimens, particularly mefloquine; hence the discontinuation. 34 Another important issue is the use of primaquine terminal prophylaxis. This procedure seems to be prescribed only within several coalition contingents.…”
Section: Chemoprophylaxis Compliance and Tolerabilitymentioning
confidence: 99%
“…The importance of this issue is understood by considering the fact that malaria incidence rate and its management can be assessed by the mathematical model such as "basic reproductive rate" ( R 0 ) [ 80 ] which has been used for the malaria risk assessment. R 0 is calculated using the formula [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of this issue is understood by considering the fact that malaria incidence rate and its management can be assessed by the mathematical model such as "basic reproductive rate" ( R 0 ) [ 80 ] which has been used for the malaria risk assessment. R 0 is calculated using the formula [ 80 ]. This is very important to note that changes in the life table parameters affect the density ( m ) and probability of living ( p ) of Anopheles mosquitoes, the two most important components of the disease reproduction rate ( R 0 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, living places on the camp are sealed to vectors (mosquito nets and frequent spraying insecticides). Third, establish a larval source management in the camps and local area surrounding of the camps that had been considered the most important step to fight vector-borne disease [48,49]. For example, military camps are not living at an isolated location from the local community.…”
Section: Figure 1 Malaria and Dengue Postermentioning
confidence: 99%